Contribución de las zonas francas permanentes en la evolución del comercio intraindustrial de Colombia (2000-2017) (2021)
Colombia's economic diversification process has not shown broad signs of growth, since such diversification is not yet represented in a commercial relationship that takes advantage of economies of scale or has less dependence on comparative advantages, which calls into question the mechanisms to promote economic diversification, including free zones; Therefore, this work seeks to determine what has been the contribution of permanent free zones in the evolution of Colombian intra-industrial trade. What are permanent free zones and how they are made up was explained; The evolution of intra-industry trade in Colombia was also analyzed and an econometric model was developed where the relationship between intra-industry trade and permanent free trade zones was compared to determine its relevance in intra-industry trade.